Cross-layer design and performance analysis of TDMA-based backhaul network - Saeed, Rashid Abdelhaleem; Mohd Yusof, Zulkarnain; Musa, Anuar (World Scientific and Engineering Academy and Society, 2009)
The needs for bridging of digital divide in rural communities and the economics of currently available broadband access technologies motivate for innovate and deploy new system designs and applications. The widely available and flexible WiFi technique meets the cost and suitability targets for rural broadband applications. To cope with the special requirements of rural communication, amendments of 802.11 standards at the MAC protocol level has been introduced. These amendments were important due to the shortcomings of WiFi over long distances under the power constraints. This paper proposes a new 802.11 point-to-multipoint (PMP) technique based on TDD/TDMA technique, this by using one of the access points in the system as centralized/gateway point to the others APs. The discussion includes the TDMA design, architecture on top of the conventional 802.11 MAC. The protocol convergence at the gateway between the access network and the backhaul is also presented. The simulation results present the performance analysis and validate the efficiency of the proposed scheme.